The Physical Activity of Gymnasium and Secondary Education Teachers - Andrzej Soroka; Joanna Baj-Korpak (Lesya Ukrainka Volyn National University, 2017)
Despite a noticeable increase in health awareness of active participation in physical culture, the vast majority of society still does not see a dependency between health and physical activeness. Only a few consider the lack of movement as one of the most harmful factors. Many researches, both Polish and foreign, point to insufficient level of physical activeness among citizens of the European Union, also including Polish ones. The report was aimed at determining the level of declared physical activity of gymnasium and secondary education teachers from Bialski region. In addition, an attempt was made to assess the impact of such variables as sex and subject taught on the level of respondents' physical activeness. There was applied a method of diagnostic survey using an IPAQ questionnaire (International Physical Activity Questionnaire) - short version, last 7 days. The research material consisted of 221 randomly selected gymnasium and secondary school teachers from Bialski region. Due to the subject taught, respondents were divided into two groups: physical education teachers (n=76) and teachers of other subjects (n=145). The largest percentage of groups surveyed consisted of people who had a sufficient level of physical activity, whilst the one third met the criteria of the high level. Only physical activeness of moderate nature significantly differentiated groups surveyed in favour of physical education teachers. Taking sex as a criterion of division of the population surveyed, among the women, a considerable differentiation appeared in the area of walking, whereas the male population did not show significant differences only in the area of intense activity.